Inverse-closed Banach subalgebras of higher-dimensional non-commutative tori - Gröchenig, Karlheinz; Leinert, Michael (Studia mathematica <Warszawa>, 2016)
We give a systematic construction of inverse-closed (Banach) subalgebras in general higher-dimensional non-commutative tori.